Thermal visualization of Ostwald-de Waele liquid in wavy trapezoidal cavity: Effect of undulation and amplitude. (January 2022) - Ahmad, Hijaz; Mahmood, Rashid; Hafeez, Muhammad Bilal; Hussain Majeed, Afraz; Askar, Sameh; Shahzad, Hasan
Abstract: The present study is concerned with the numerical simulations of Ostwald-de Waele fluid flow in a wavy trapezoidal cavity in the presence of a heated cylinder situated at the center of the cavity. The work consists in characterizing the mixed convection as a function of the intensity of heat flow. The flow behaviour and temperature distribution in a cavity are the main focus of this study. The lower wall of the cavity is fixed and heated while the wavy surface is insulated and moves with a constant speed. The sloping walls are kept cold and are subject to zero no-slip conditions for velocity components. The whole setup is modeled as a set of coupled partial differential equations and is solved by the Finite Element Method. For pressure and velocity approximations, we use the stable finite element pair P 2 − P 1, while for temperature approximation we use the space of linear polynomial as P 1 . The ranges of the parameters involved in the study are the Ostwald-de Wale index ( 0.5 ≤ n ≤ 1.5 ), Prandlt number ( 1 ≤ Pr ≤ 10 ), Grashof number ( 100 ≤ G r ≤ 1000 ), the number of undulation ( 0 ≤ λ ≤ 4 ), and the non-dimensional amplitude of the wavy surface ( 0.02 ≤ A ≤ 0.06 ) . The major findings of the study are shown using velocity profile, streamlines, and isotherms. Moreover, the kinetic energy and average ( N u a v g ) Nusselt number is determined for various values of the parameters involved.